Peningkatan Hasil Belajar Sosiologi Menggunakan Model Pembelajaran Make a Match - Matilde Triyanti Mensi Loe (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This study aims to obtain information regarding the impact of learning sociology using “a make-a-match” in the X grades at SMA Negeri 1 Atambua. This study is an action research study (PTK) that is being conducted in order to improve student learning. The subject of this study is 36 students of X grades majoring in Social Science 4 at SMA Negeri 1 Atambua in the academic year 2022/2023. This study is being conducted in two stages, where each rule will be carried out twice, and the final rule will be an evaluation or final test. The findings showed that applying the “make a match” learning model in sociology subjects improved student learning outcomes. It can be shown that the overall score of student learning outcomes at the Pre-cycle meeting is 2,422 with an average of 67.27, whereas the total value of student learning outcomes at Cycle I is 2,612 with an average of 72.55. Meanwhile, the number of results in cycle II is 3,102, with an average of 86 16. This result met the researcher's Success Criteria, 80% higher than the Minimum Completeness Criteria, 73.